2020
DOI: 10.7554/elife.56095
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory osteolysis is regulated by site-specific ISGylation of the scaffold protein NEMO

Abstract: Inflammatory osteolysis is governed by exacerbated osteoclastogenesis. Ample evidence points to central role of NF-κB in such pathologic responses, yet the precise mechanisms underpinning specificity of these responses remain unclear. We propose that motifs of the scaffold protein IKKγ/NEMO partly facilitate such functions. As proof-of-principle, we used site-specific mutagenesis to examine the role of NEMO in mediating RANKL-induced signaling in mouse bone marrow macrophages, known as osteoclast precursors. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 77 publications
2
14
0
Order By: Relevance
“…Some studies have shown that TGF-β1 directly down-regulates NFATc1 activity by blocking the p65 in the receptor activator and then inhibits the generation and bone resorption of osteoclasts ( Figure 2 ) (Tokunaga et al, 2020 ). Recently, the role of the NEMO protein (a core component of the NF-kB signaling pathway) in mouse bone marrow macrophages was investigated that if the lysine-270 (NEMO-Lys270) in NEMO protein was mutated to Ala, the NF-kB signal in bone marrow macrophages would lose control, leading to the accelerated production of osteoclasts (Adapala et al, 2020 ). What's more, studies have found that the overexpression of cr6 interaction factor-1 (Crif1) in mouse BMSCs can increase the secretion of RANKL through the cAMP/PKA pathway, and then combine with RANK on macrophages to promote the formation of osteoclasts in vitro (Xiang et al, 2020 ).…”
Section: Communications Between Macrophages and Bone Cellsmentioning
confidence: 99%
“…Some studies have shown that TGF-β1 directly down-regulates NFATc1 activity by blocking the p65 in the receptor activator and then inhibits the generation and bone resorption of osteoclasts ( Figure 2 ) (Tokunaga et al, 2020 ). Recently, the role of the NEMO protein (a core component of the NF-kB signaling pathway) in mouse bone marrow macrophages was investigated that if the lysine-270 (NEMO-Lys270) in NEMO protein was mutated to Ala, the NF-kB signal in bone marrow macrophages would lose control, leading to the accelerated production of osteoclasts (Adapala et al, 2020 ). What's more, studies have found that the overexpression of cr6 interaction factor-1 (Crif1) in mouse BMSCs can increase the secretion of RANKL through the cAMP/PKA pathway, and then combine with RANK on macrophages to promote the formation of osteoclasts in vitro (Xiang et al, 2020 ).…”
Section: Communications Between Macrophages and Bone Cellsmentioning
confidence: 99%
“…For example, intermittent fasting and rapamycin as autophagy promoting compounds have gained interest recently as modalities for driving protective autophagy ( Johnson et al, 2013 ; Mattson and de Cabo, 2020 ). Our prior work has also demonstrated that autophagy can also regulate inflammatory responses through modulation of NF-κB and other pathways ( Adapala et al, 2020 ), which may be involved in the anti-inflammatory effect of glutamine deprivation. Our future work will focus on understanding the role of ATF4 stress response system and autophagy in the modulation of chondrocyte inflammatory response and NF-κB activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, intermittent fasting and rapamycin as autophagy promoting compounds have gained interest recently as modalities for driving protective-autophagy(Johnson, Rabinovitch, & Kaeberlein, 2013; Mattson & de Cabo, 2020). Our prior work has also displayed that autophagy can also regulate inflammatory responses through modulation of NF-κB and other pathways(Adapala et al, 2020), which may be involved in the anti-inflammatory effect of glutamine deprivation. Our future work will focus on understanding the role of ATF4 stress response system and autophagy in the modulation of chondrocyte inflammatory response and NF-κB activity.…”
Section: Discussionmentioning
confidence: 99%